Relação 18:3n3/18:2n6 sobre a digestibilidade de ácidos graxos em pacu - Segura, Julio Guerra; Campanharo, João Carlos [UNESP]; De Oliveira, Kátia Rodrigues Batista [UNESP]; Natori, Mariene Miyoko; De Medeiros, Adja Cristina Lira; Viegas, Elisabete Maria Macedo (Boletim do Instituto de Pesca, 2017)
The objective of this work was to determine the effect of diets with this 18:3n3/18:2n6 ratios: 2.98; 1.68; 1.03; 0.61 and 0.35 (treatments 1 to 5 respectively), on the apparent digestibility coefficients (ADC) of fatty acids in vegetable-based diets for pacu juveniles (Piaractus mesopotamicus). Eighteen groups of 16 fish each were fed for 34 days with a control diet containing tilapia oil as sole ingredient of animal origin (treatment 6). In a second phase, for 72 days, each diet was fed to 3 random groups, and finally the fatty acid ADC’s were calculated. The control diet produced the highest ADC of saturated fatty acids (97.3%) and monounsaturated fatty acids (98.24%); and treatment 1, the highest polyunsaturated fatty acids (99.25%) and 18:3n3 (99.83%) ADC’s. The ADC of 18: 3n3 varied in a decreasing manner according to the variation of the ratio 18:3n3/18:2n6 and was always higher than the ADC of 18:2n6, despite the non-specific action of lipases. We conclude that the ADC’s of fatty acids, or groups of them, increase as their degree of unsaturation and concentration in the diet increases, and, the fluidity of the oil affects the ADC of 18:3n3 -ALA and not of 18:2n6 - LA when these are the only poly-unsaturated fatty acids.
18:3n3/18:2n6 ratio on fatty acid digestibility in pacu
Keywords: Alpha linolenic acid; Aquaculture; Linseed oil; Omega-3; Piaractus mesopotamicus; Vegetable-based aquafeeds